Peran Gender dalam Memoderasi Pengaruh Mindset Bertumbuh terhadap Grit - Yosua Victor Putra Widodo; Sunawan Sunawan (Journal of Society Counseling, 2026)
Grit is a crucial psychological asset for college students facing dynamic academic challenges; however, empirical evidence suggests that many students still exhibit suboptimal levels of grit. This study aims to explore the influence of a growth mindset on grit and to examine the moderating role of gender in this relationship. A quantitative correlational design was used in this study. The sample consisted of 328 undergraduate students in the Faculty of Education and Psychology at Semarang State University, selected using a proportional stratified random sampling method. Data were collected using the Grit Scale (Grit-O) and the Revised Implicit Theories of Intelligence Scale and analyzed using Hayes' PROCESS Model 1. The results indicate that growth mindset significantly and positively predicts students’ grit (β = 0.38, p = 0.01 < 0,05). However, gender does not significantly moderate this relationship (p = 0.73 > 0,05). These findings suggest that the mechanism of a growth mindset in fostering grit is universal and functions similarly for both male and female students. These results imply that university counselors can design inclusive growth mindset interventions to enhance student grit without the need for differentiation based on gender.